Nutrition in transition: Historical cohort analysis summarising trends in under- A nd over-nutrition among pregnant women in a marginalised population along the Thailand-Myanmar border from 1986 to 2016. - Ahmar H. Hashmi (2019)
© The Authors 2019. The objective of this study is to summarise trends in under- A nd over-nutrition in pregnant women on the Thailand-Myanmar border. Refugees contributed data from 1986-2016 and migrants from 1999-2016 for weight at first antenatal consultation. Body mass index (BMI) and gestational weight gain (GWG) data were available during 2004-2016 when height was routinely measured. Risk factors for low and high BMI were analysed for <18.5 kg/m 2 or ≥23 kg/m 2 , respectively. A total of 48,062 pregnancies over 30 years were available for weight analysis and 14,646 pregnancies over 13 years (2004-2016) had BMI measured in first trimester (<14 weeks' gestational age). Mean weight at first antenatal consultation in any trimester increased over the 30-year period by 2.0 to 5.2 kg for all women. First trimester BMI has been increasing on average by 0.5 kg/m 2 for refugees and 0.6 kg/m 2 for migrants, every five years. The proportion of women with low BMI in the first trimester decreased from 16.7% to 12.7% for refugees and 23.1% to 20.2%for migrants, whereas high BMI increased markedly from 16.9% to 33.2% for refugees and 12.3% to 28.4% for migrants. Multivariate analysis demonstrated low BMI as positively associated with being Burman, Muslim, primigravid, having malaria during pregnancy and smoking, and negatively associated with refugee as opposed to migrant status. High BMI was positively associated with being Muslim and literate, and negatively associated with age, primigravida, malaria, anaemia and smoking. GWG (mean±SD, kg) was 10.0±3.4, 9.5±3.6 and 8.3±4.3, for low, normal and high WHO BMI categories for Asians, respectively.